The catalytic activity for ginkgolic acid biodegradation, homology modeling and molecular dynamic simulation of salicylic acid decarboxylase. (August 2018) - Hu, Yanying; Hua, Qingyuan; Sun, Guojuan; Shi, Kunpeng; Zhang, Huitu; Zhao, Kai; Jia, Shiru; Dai, Yujie; Wu, Qingli
Graphical abstract: Highlights: The salicylic acid decarboxylase (SDC) was found to have the activity to degradate ginkgolic acid. The SDC structure was constructed by homology modeling. The complexes of SDC with ligands were obtained by molecular docking and molecular dynamics. SDC may have a Zn 2+ catalytic active center according to the homology model structure and experiments. Abstract: The toxic ginkgolic acids are the main safety concern for the application of Ginkgo biloba . In this study, the degradation ability of salicylic acid decarboxylase (SDC) for ginkgolic acids was examined using ginkgolic acid C15:1 as a substrate. The results indicated that the content of ginkgolic acid C15:1 in Ginkgo biloba seeds was significantly decreased after 5 h treatment with SDC at 40 °Cand pH 5.5. In order to explore the structure of SDC and the interaction between SDC and substrates, homology modeling, molecular docking and molecular dynamics were performed. The results showed that SDC might also have a catalytic active center containing a Zn 2+ . Compared with the template structure of 2, 6-dihydroxybenzoate decarboxylase, the residues surrounding the binding pocket, His10, Phe23 and Phe290, were replaced by Ala10, Tyr27 and Tyr301 in the homology constructed structure of SDC, respectively. These differences may significantly affect the substrates adaptability of SDC for salicylic acid derivatives.